Analisis Stabilitas Transien Tegangan dan Frekuensi pada Sistem Pembangkit Listrik Tenaga Uap - Anang Dasa Novfowan; Wijaya Kusuma; Mochammad Mieftah (Politeknik Negeri Malang, 2021)
Electrical energy generated also comes from several energy, namely water, steam, nuclear, etc. In Indonesia the type ofsteam power plant is a type of power plant that is widely used, where one of the crucial problems that are often encountered in this generation system, namely the problem of stability. The stability of the electric power system is the ability of the system to return to normal or steady operation after a large load load switching or interference. Disruption or load switching that exist in the system must be muted and aligned in a certain time to be said to be stable. Causes of instability are disruptions in the form of large capacity load switching, and the type of interference. One aspect that affects the stability itself is the transient stability. The transient stability is related to the sudden influx of large-capacity loads and affect the performance of the generator, therefore it is necessary to analyze the voltage and frequency transient stability for the evaluation of the capability of the electrical system so that the system maintains the continuity of the supply of electrical energy to the load normally. Based on the research results, the current flowing before the disturbance of 98.9 A and current disturbance of 145.2 kA. This causes the voltage response to decrease 50% of the nominal, and the frequency increases to 50.36 Hz. The time required from the disturbance condition to a stable condition within 5 seconds.